2017
DOI: 10.1039/c6fd00238b
|View full text |Cite
|
Sign up to set email alerts
|

Electrovariable gold nanoparticle films at liquid–liquid interfaces: from redox electrocatalysis to Marangoni-shutters

Abstract: Control over the physical properties of nanoparticle assemblies at a liquid-liquid interface is a key technological advancement to realize the dream of smart electrovariable nanosystems.Electrified interfaces, such as the interface between two immiscible electrolytes solutions (ITIES), are almost an ideal platform for realizing this dream. Here, we show that the Galvani potential difference across soft interfaces can be effectively used to manipulate: (i) the reactivity of gold nanoparticle assemblies through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…111 Also, IMPS has been used recently to study the role of the NPs as redox electrocatalysts in interfacial reaction between DMFc and water soluble zwitter-porphyrin (ZnDMPyDSPP). 112 Authors demonstrated that the presence of gold nanoparticles at ITIES negates kinetic limitation for the interfacial reactions, which corroborates with previous studies. 9,84 An interesting new field is photo-induced redox electrocatalysis [113][114][115] and redox catalysis 116,117 for synthesis of solar fuels.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…111 Also, IMPS has been used recently to study the role of the NPs as redox electrocatalysts in interfacial reaction between DMFc and water soluble zwitter-porphyrin (ZnDMPyDSPP). 112 Authors demonstrated that the presence of gold nanoparticles at ITIES negates kinetic limitation for the interfacial reactions, which corroborates with previous studies. 9,84 An interesting new field is photo-induced redox electrocatalysis [113][114][115] and redox catalysis 116,117 for synthesis of solar fuels.…”
supporting
confidence: 89%
“…In this case, surface second harmonic generation (SSHG) and time-resolved SSHG may provide detailed information on molecule configurations and positioning at the interface, whereas dynamics of photoresponses (kinetic constants of electron transfer) upon heterogeneous quenching at the ITIES can be probed by intensity modulated photocurrent spectroscopy (IMPS), as was shown for of ZnTPPC and ferrocene derivatives . Also, IMPS has been used recently to study the role of NPs as redox electrocatalysts in interfacial reaction between DMFc and water-soluble zwitter-porphyrin (ZnDMPyDSPP) . The authors demonstrated that the presence of gold NPs at ITIES negates kinetic limitation for the interfacial reactions, which corroborates with previous studies. , …”
mentioning
confidence: 99%
“…[21,23,24] Usually the surface is not homogeneously covered, significant aggregation of particles takes place at the interface and potential cycling can induce movement of the particles generating an interfacial convection (interfacial stirring). [25] Citrate ions are typically used to stabilize AuNP suspensions in bulk aqueous solutions. [26] However, such suspensions are very stable and, due to inter-particle electrostatic repulsion, the AuNPs rarely deposit in significant numbers at the L|L interface on contacting the aqueous phase with an immiscible organic solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Controlled assembly of molecules and nano-objects and in situ electrogeneration of nanomaterials and membranes are possible [10]. It was shown that the Galvani potential difference at the ITIES can be effectively used to manipulate the reactivity of gold nanoparticles by varying the Fermi level (both chemically and electrochemically) or the position of nanoparticles at the liquid-liquid interface [62][63][64]. It was established that the classical electroanalytical method with a solid electrode can be directly transferred to ITIES, which makes it possible to easily trace and interpret reversible charge transfer reactions [65].…”
Section: Interfacial Formationsmentioning
confidence: 99%